The Effectiveness of Narrative Therapy in Improving Academic Vitality and Resilience of Students with Mother Heads of Households - Bakhtyarirenani Renani, Azam; Kordmirza Nikoozadeh, Ezzatollah (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: Social and psychological problems, such as academic failure and discouragement, can impose significant financial and social costs on families and society if the issues faced by students with head-of-household women are not addressed. The present study aimed to determine the effectiveness of narrative therapy in improving the resilience and vitality of students with head-of-household women. Materials and Methods: The study employed a semi-experimental design with a pretest-posttest approach and a control group. The statistical population consisted of all female students with head-of-household women in the second-grade high schools in Isfahan City during the academic year 2022-2023. According to the convenience sampling method, 30 students were selected as the statistical sample, with 15 randomly assigned to the experimental group and 15 to the control group. Data collection was performed using the Academic Vitality Scale and the Resilience Scale. White and Epston’s (1990) narrative therapy program consisted of eight one-hour sessions, held twice a week, for the experimental group after the implementation of the questionnaires. Univariate analysis of covariance (ANOVA) was also utilized to test the hypotheses. Results: Narrative therapy training was effective in increasing the academic vitality and resilience of students, particularly those from households headed by women, and students in the experimental group had significantly higher academic vitality and resilience than those in the control group at the post-test. Conclusion: Based on the results of the present research, narrative therapy training is efficacious in improving the resilience and happiness of students with head-of-household women, and this training can help address their problems. Furthermore, the counselors’ and specialists’ knowledge about this therapy can be helpful.